PENGARUH HUMAN RESOURCE DEVELOPMENT, FOLLOWER-LEADER GOAL CONGRUENCE, WORK LIFE BALANCE, DAN JOB SECURITY TERHADAP ORGANIZATIONAL COMMITMENT PADA PNS DI KANTOR POLISI WILAYAH JAKARTA SELATAN - Kania Reskia Ananditha; Desak Gede Mahira Putri; Netania Emilisa; Nabillah Chairunisah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the effect of Human Resource Development, Follower-Leader Goal Congruence, Work Life Balance, and Job Security on Organizational Commitment. The research was conducted using a quantitative approach and survey method by taking samples from employees at several police stations in the South Jakarta area. Data were analyzed using multiple regression analysis techniques. There were 170 samples collected. The results showed that Follower-Leader Goal Congruence, Work Life Balance, Job Security significantly influenced Organizational Commitment. However, Human Resource Development has no effect on Organizational Commitment. This shows that employees who have high levels of Follower-Leader Goal Congruence, high Work Life Balance, and high Job Security tend to have a higher commitment to the organization where they work. This research provides practical implications for companies in increasing employee commitment. Company management can pay attention to the factors that influence employee commitment. This research also provides a theoretical contribution to the literature on organizations because it reveals the importance of psychological factors in shaping employee commitment.